Missed Opportunities : The High Cost of Not Educating Girls - Wodon, Quentin; Montenegro, Claudio; Nguyen, Hoa; Onagoruwa, Adenike (World Bank, Washington, DC, 2018)
Too many girls drop out of school prematurely, especially in low income countries. Low educational attainment for girls has negative consequences not only for them, but also for their children and household, as well as for their community and society. This study documents the potential impacts of educational attainment for girls and women in six domains: (1) earnings and standards of living; (2) child marriage and early childbearing; (3) fertility and population growth; (4) health, nutrition, and well-being; (5) agency and decision-making; and (6) social capital and institutions. The results are sobering: the potential economic and social costs of not educating girls are large. Low educational attainment reduces expected earnings in adulthood, and it depresses labor force participation, leading to lower standards of living. When girls drop out of school prematurely, they are much more likely to marry as children, and have their first child before the age of 18 when they may not yet be ready to be wife and mothers. This in turn is associated with higher rates of fertility and population growth, which in low income countries are major impediments for reaping the benefits of the demographic dividend. Low educational attainment is also associated with worse health and nutrition outcomes for women and their children, leading among others to higher under-five mortality and stunting. Girls who drop out of school also suffer in adulthood from a lack of agency and decision-making ability within the household, and in society more generally. They are also less likely to report engaging in altruistic behaviors such as donating to charity, volunteering, or helping others. Finally, when girls and women are better educated, they may be better able to assess the quality of the basic services they rely on and the quality of their country’s institutions and leaders. These negative impacts have large economic costs, leading among others to losses in human capital wealth (future lifetime earnings of the labor force) estimated at $15 trillion to $30 trillion. Educating girls is not only the right thing to do: it is also a smart economic investment.